Differential degradation of RNA species by autophagy-related pathways in Arabidopsis. (9th July 2021) - Hickl, Daniel; Drews, Franziska; Girke, Christopher; Zimmer, David; Mühlhaus, Timo; Hauth, Jan; Nordström, Karl; Trentmann, Oliver; Neuhaus, Ekkehard H; Scheuring, David; Fehlmann, Tobias; Keller, Andreas; et al.
Abstract : RNA composition of mesophyll vacuoles revealed all types of RNAs and autophagy played a key role in regulating vacuolar transport and degradation of plastid-encoded photosynthesis-related genes Abstract: The plant vacuole recycles proteins and RNA delivered to it by autophagy. In this study, by isolating intact vacuoles from Arabidopsis plants, followed by subsequent RNA purification, and deep sequencing, we provide a comprehensive characterization of Arabidopsis vacuolar RNAome. In the vacuolar RNAome, we detected ribosomal RNAs, transfer RNAs, including those of chloroplast origin, and in addition small RNA types. As autophagy is a main mechanism for the transport of RNA to the vacuole, atg5-1 mutants deficient in autophagy were included in our analysis. We observed severely reduced amounts of most chloroplast-derived RNA species in these mutants. Comparisons with cellular RNA composition provided an indication of possible up-regulation of alternative RNA breakdown pathways. By contrast, vacuolar RNA processing and composition in plants lacking vacuolar ribonuclease 2, involved in cellular RNA homeostasis, only showed minor alterations, possibly because of the presence of further so far unknown vacuolar RNase species. Among the small RNA types, we detected mature miRNAs in all vacuolar preparations but at much lower frequency in atg5-1, raising the possibility of a biological role for vacuolar miRNAs.